1996
DOI: 10.1007/s001130050055
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich und Ergebnis von Schultereckgelenkverletzungen II. und III. Grades

Abstract: Eighty-five patients with grade 2 or grade 3 sprains of the acromioclavicular (AC) joint were evaluated clinically and radiographically 32 months after injury. Group I included 34 patients with grade 2 sprains (Tossy II) and group II included 51 patients with grade 3 injuries (Tossy III). In group I, 15 patients were treated surgically (group Ia) and 19 patients were treated conservatively (group Ib), while in group II, 41 patients were treated surgically (group IIa) and 10 patients were treated conservatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
3
0
3
Order By: Relevance
“…This suggests that a higher number of radiographic abnormalities in the surgical group might not be a valid argument for conservative treatment. This is in accordance with previous studies, which demonstrated that radiological abnormalities after surgery were often not clinically relevant in patients [2,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that a higher number of radiographic abnormalities in the surgical group might not be a valid argument for conservative treatment. This is in accordance with previous studies, which demonstrated that radiological abnormalities after surgery were often not clinically relevant in patients [2,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…Clinical redislocations occur in 3-43% of the cases [9,12,14,26]. On X-rays, a subluxation is present in 17%, and 3% have a complete redislocation [9,10,26,27]. Our previous experiences have also shown that, if redislocation appears after operative treatment, the number of excellent and good results drops from 60% to 30% (p < 0.05; Figure 4) [20].…”
Section: Resultsmentioning
confidence: 98%
“…So, operative treatments do not guarantee maintenance of reduction. Clinical redislocations occur in 3-43% of the cases [9,12,14,26]. On X-rays, a subluxation is present in 17%, and 3% have a complete redislocation [9,10,26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Zwei neuere Untersuchungen [29,32] wurden nach dem ¹constant scoreª durchgeführt. Obwohl die konservative Therapie in 9 der 10 Studien einheitlich in einer kurzzeitigen Ruhigstellung von 2±4 Wochen und anschlieûender funktioneller Therapie bestand, sind die operativen Verfahren sehr unterschiedlich.…”
Section: Retrospektivstudienunclassified
“…Übereinstimmend wird in allen Nachuntersuchungen ein verbliebener Hochstand der lateralen Clavicula in bis zu 90 % nach konservativer Therapie angegeben [29]. In bis zu 44 % wurden diese Befunde auch nach operativer Therapie erhoben.…”
Section: Retrospektivstudienunclassified